2010
DOI: 10.1007/s10533-010-9437-2
|View full text |Cite
|
Sign up to set email alerts
|

Importance of soil calcium for composition of understory vegetation in boreal forests of Finnish Lapland

Abstract: To focus conservation efforts into forest areas with high biodiversity, more information is needed about soil-vegetation dependencies in Finnish Lapland. We studied understory vegetation and soil variables along a transect across a felsic-mafic lithological sequence in central Finnish Lapland. At 119 northern boreal forest sites, coverages of understory vegetation, several mineral soil chemical elements, soil electrical conductivity, pH, and dielectric permittivity, as a measure of soil volumetric water conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 55 publications
2
15
0
2
Order By: Relevance
“…McBride et al (1990) found EC a at red oak (Quercus rubra L.) sites to be strongly correlated with soil attributes associated with forest soil quality, such as exchangeable Ca, Mg and CEC. In a similar way, we have found a positive correlation between the field-measured soil EC a and concentrations of Ca, Mg and Na, but a negative correlation with Al in forest soils in Finnish Lapland (Närhi et al 2010b). With known distribution of geochemical elements in tills, the large quantity of measured soil EC a and SWC provides us with a justified basis to assess relative differences in micro-site soil regimes and natural recruitment of Norway spruce at intensively managed sites in Lapland.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…McBride et al (1990) found EC a at red oak (Quercus rubra L.) sites to be strongly correlated with soil attributes associated with forest soil quality, such as exchangeable Ca, Mg and CEC. In a similar way, we have found a positive correlation between the field-measured soil EC a and concentrations of Ca, Mg and Na, but a negative correlation with Al in forest soils in Finnish Lapland (Närhi et al 2010b). With known distribution of geochemical elements in tills, the large quantity of measured soil EC a and SWC provides us with a justified basis to assess relative differences in micro-site soil regimes and natural recruitment of Norway spruce at intensively managed sites in Lapland.…”
Section: Introductionsupporting
confidence: 76%
“…They conjectured that soil degradation was coincidental with leaching of soil Ca and Mg. In addition, Närhi et al (2010b) have found a positive correlation between the field measured soil EC a and laboratory analyzed (plant available) Ca and Mg, whereas Al was negatively correlated to EC a . The reduction in the soil Ca and Mg supply caused by clear-cut and subsequent site preparation (Van Cleve and Dyrness 1983) significantly reduces the growth potential of shallow-rooted Norway spruce and contributes to low survival rate observed with the exposed mineral soil ( Fig.…”
Section: Edaphic Constraints and Spruce Stockingmentioning
confidence: 87%
“…Kalliola 1973;Sutinen et al 2002Sutinen et al , 2012Närhi et al 2011) and the concentrations of plant elements generally reflect the element composition of the bedrock beneath the growing site (Närhi et al 2013). It has been shown that the forest vegetation communities of Finnish Lapland are intimately related to soil chemistry; Ca-concentration being the major variable in determining plant diversity (Närhi et al 2011). For example, herb-rich forests grow in alkaline soils originated from Ca-rich rocks like dolomite and greenstones and many demanding calcifuge species colonize these fertile herb-rich forests (Kalliola 1973).…”
Section: Moose Damage Was Concentrated In the Areas Of Nutrient-rich mentioning
confidence: 99%
“…In addition, the bedrock beneath the soil affects soil fertility (Kalliola 1973;Sutinen et al 2011). The bedrock erodes by physical and chemical factors and the weathered material together with organic material constitute the soil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation